2020
DOI: 10.3897/zookeys.925.47820
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome sequence of Scolopendra mutilans L. Koch, 1878 (Scolopendromorpha, Scolopendridae), with a comparative analysis of other centipede genomes

Abstract: Scolopendra mutilans L. Koch, 1878 is an important Chinese animal with thousands of years of medicinal history. However, the genomic information of this species is limited, which hinders its further application. Here, the complete mitochondrial genome (mitogenome) of S. mutilans was sequenced and assembled by next-generation sequencing. The genome is 15,011 bp in length, consisting of 13 protein-coding genes (PCGs), 14 tRNA genes, and two rRNA genes. Most PCGs start with the ATN initiation codon, and all PCGs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…Moreover, the monophyly of the ordinal groups Scutigeromorpha, Scolopendromorpha, Geophilomorpha, and Lithobiomorpha was forcefully advocated in both BI and ML trees. Then, the Scolopendromorpha was supported as a sister clade of (Lithobiomorpha + Geophilomorpha), consistent with the research of Hu et al [59], although it was in conflict with a well-corroborated scheme of interrelationships for Pleurostigmophora that Lithobiomorpha was the sister clade of (Scolopendromorpha + Geophilomorpha) [4][5][6][7]79,80]. For Scutigeromorpha, we found that all T. tuberculata clustered together and the clade of (((T. tuberculata NC + T. tuberculata JN) + T. tuberculata NY) + T. tuberculata DL) was the sister clade of S. coleoptrata.…”
Section: Phylogenetic Analysessupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, the monophyly of the ordinal groups Scutigeromorpha, Scolopendromorpha, Geophilomorpha, and Lithobiomorpha was forcefully advocated in both BI and ML trees. Then, the Scolopendromorpha was supported as a sister clade of (Lithobiomorpha + Geophilomorpha), consistent with the research of Hu et al [59], although it was in conflict with a well-corroborated scheme of interrelationships for Pleurostigmophora that Lithobiomorpha was the sister clade of (Scolopendromorpha + Geophilomorpha) [4][5][6][7]79,80]. For Scutigeromorpha, we found that all T. tuberculata clustered together and the clade of (((T. tuberculata NC + T. tuberculata JN) + T. tuberculata NY) + T. tuberculata DL) was the sister clade of S. coleoptrata.…”
Section: Phylogenetic Analysessupporting
confidence: 88%
“…To date, the only mitochondrial genome of Chilopoda, Scutigera coleoptrata [ 56 ], was public in the NCBI. In this study, the mitochondrial genomes of 17 chilopods including T. tuberculata , S. coleoptrata [ 56 ], two Geophilomorpha species [ 57 ], four Scolopendromorpha species [ 58 , 59 ] as well as three Lithobiomorphas species [ 60 , 61 , 62 ] were selected as the ingroup taxa in order to investigate the phylogenetic relationships within Chilopoda. Since the diplopod was considered as a more distant and suitable outgroup to root the centipede tree [ 8 , 11 ], Anaulaciulus koreanus (Helminthomorpha: Julidae) [ 63 ] and Spirobolus bungii (Helminthomorpha: Spirobolidae) (MT767838) were chosen as the outgroup taxa for phylogenetic analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Characterized by small size, stable gene content, high evolutionary rate, relatively conserved gene arrangement, high information content, and maternal inheritance, animal mitogenomes are powerful tools used to investigate molecular evolution, phylogenetic relationships, and protective biology for many animals ( Yu et al 2017 ; Zhang et al 2018 ; Song et al 2019 ; Hu et al 2020 ; Wu et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…All PCGs started with ATN. The AT contents of the PCGs of Chilopoda ranged from 59.6% ( S. dehaani ) [ 43 ] to 77.2% ( S. mutilans ) [ 41 ]. The A + T contents of the PCGs in the mitogenomes of M. marmoratus and S. subspinipes were 67.1% and 71.6%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, the mitochondrial gene orders of Scolopendra dehaani , Scolopendra mutilans , S. maritima , Scutigera coleoptrata, and Spirobolus bungii were distinctly different from those of any other myriapod species [ 42 , 43 , 44 , 45 ]. A high rate of rearrangement makes the Myriapoda an ideal class group for exploring the interactions between gene rearrangements and phylogenetic relationships.…”
Section: Introductionmentioning
confidence: 99%